From Education to Democracy? - Acemoglu, Daron; Johnson, Simon; Robinson, James A; Yared, Pierre (American Economic Review, 2005)
The conventional wisdom views high levels of education as a prerequisite for democracy. This paper shows that existing evidence for this view is based on crosssectional correlations, which disappear once we look at within-country variation. In other words, there is no evidence that countries that increase their education are more likely to become democratic.